Strategi Pengelolaan Kelas di SDN Gondangrejo - Mulati Ningsih; Sukma Wijayanto (Prosiding University Research Colloquium, 2021)
This study aims to explore teacher attitudes in maximizing class potential; classmanagement inhibiting factors; teacher's efforts in overcoming classroom managementproblems; and classroom management strategies. This case study was conducted at SDNGondangrejo, and used a qualitative approach. The data from this study were obtainedthrough interviews and observations regarding classroom management. The results ofthis study indicate that in classroom management the teacher functions as a counselor,facilitator, motivator, demonstrator, and evaluator. Therefore, teachers are able to analyze problems surrounding students, teachers, as well as the physical and socio-emotional environment in the classroom. Regarding this, teachers try to apply preventive and corrective. Teachers tend to use an eclectic approach, namely applying two or moreapproaches at the same time. Thus, it is hoped that the eclectic approach can assistteachers in improving the quality of choosing an approach that allows them to overcomeproblems regarding classroom management